Modelling the intentions of using E-book among educators / Afifah Suraya Ismail and Julaikha Seri Ayu Mat Yasin - Ismail, Afifah Suraya; Mat Yasin, Julaikha Seri Ayu (Faculty of Business and Management, 2013)
There is a growing interest in E-Books since there are advantages found when it is used, said Sohn, et.al. (n.d). Little is known on what attracts the educators to use e-book in their teachings. The purpose of this study was to study the intentions of educators in Malaysia to use E-Book (electronic book). The data from the questionnaires answered by the respondents showed the importance of counting on the intentions of using e-books. Since the printed textbooks might be irreplaceable with e-books, it is important to know the intentions for educators to consider in using it. Therefore, the aim of the study is to find out what are the intentions. The sample of this study is 100 respondents that mostly include the educators in Malaysia. We have distributed printed questionnaires to the respondents and also distributed it online. It is found that only two hypotheses were supported in this study. It can be said that ubiquity and perceived compatibility have a positive and significant effect on intention to use e-books among educators in Malaysia.